Clinical profile, sociodemographic and biochemical determinants of PICA among 1 to 5 aged children attending a tertiary care hospital - Pasupathy, Sekar; Swarna, Srujana (International Journal of Contemporary Pediatrics, 2018)
Background: The term PICA has been derived from the Latin word “MAGPIE” which is a bird that has omnivorous habit and is known for its indiscriminate preference for foods and non-foods. The aim of this study was to study the clinical profile and to determine the relationship between pica and various socio demographic determinants, serum levels of iron, zinc and calcium. Methods: This study was conducted in 51 children with PICA belonging to 1-5 years and 51 controls of same age and sex who were attending pediatrics department in SRM medical college hospital and research centre. The data regarding clinical manifestations and sociodemographic determinants were collected by questionnaires to mother. The blood samples were collected from each child involved in the study after getting consent. Then the data was analyzed by using chi-square, unpaired ‘t’ test and ANOVA analysis. Results: This study shows that PICA is commonly seen in males, bottle fed children and those belonging to nuclear family. Family history of PICA had significant association with PICA in children (p=0.05). Soil is the most common type of pica (49%) followed by paper and stone. The most common presentation is poor appetite (43.1%). The serum levels of iron and zinc were significantly low when compared to controls (P <0.001). The serum levels of iron in anemic children with pica are also significantly lower than pica children with no anemia. No significant association is seen between serum iron and zinc with number of substances or duration of ingestion or frequency of ingestion (P >0.05). Conclusions: Family history of PICA, bottle feeding, joint family has significant association with pica. Soil is the most common type of PICA. Poor appetite is the most common clinical manifestation. There is significant association between low serum levels of iron and zinc with PICA.